Proposed new interior design of Crazy Manga Store for Animation Technology Sdn Bhd at No 5 & 6 Sunway Giza, Dataran Sunway PJU 5 Kota Damansara, Petaling Jaya, Selangor Darul Ehsan / Ibrahim Abu Bakar - Abu Bakar, Ibrahim (Faculty of Architecture, Planning and Surveying, 2010)
The student’s final project of Diploma in Interior Design reveals students knowledge on all aspects in interior design from basic principle of designs to the final presentation of the proposed project. This includes understanding on the criteria of the chosen site for the proposed project, as well as knowledge on identifying structures of the existing building, along with its mechanical and electrical systems, plumbing systems and existing materials. The chosen project for the final project is to proposed new interior design of Crazy Manga Store for Animation Technology Sdn. Bhd.at No. 5 and 6 Sunway Giza, Dataran Sunway PJU 5 Kota Damansara, Petaling Jaya, Selangor Darul Ehsan. The client, Animation Technology Sdn. Bhd. is expected to increase more specialty stores throughout Malaysia, including Sabah and Sarawak.Within their long-term planning, they are also planning to open a store that sells mainly comic books.Therefore, this comic store is proposed to attract younger customers, especially children and teenagers to come to the store and buy comic books..The main product for this store is mainly a Japanese comic books or better known as manga among Japanese comic lovers. Besides, there are also other products provided such as figurines, cards, magazines, DVD animation, DVD soundtrack and cosplay merchandise.The chosen concept and image not only fulfilled client’s requirement, but also must reflect client’s character and corporate image as well as to give a positive impact to the performance of workers inside the store so that it will inculcate workers to work even harder. Plus, the chosen design style for Crazy Manga Store is based on the chosen concept for the store. Before achieving a desired design that is going to be implemented inside the store, some analytical works need to be carried out such as collecting datas from client regarding to their nature of business. Certain information are gained through the interview with the client itself, observation and internet.